The Dual Regulation Effects of ESR1/NEDD4L on SLC7A11 in Breast Cancer Under Ionizing Radiation - Liu, Rui; Liu, Lin; Bian, Yan; Zhang, Shinan; Wang, Yue; Chen, Huajian; Jiang, Xinyue; Li, Guanghui; Chen, Qing; Xue, Chang; Li, Mengke; Liu, Lianchang; et al. (Frontiers in Cell and Developmental Biology, 2022)
Radiotherapy is one of the most important treatments for breast cancer (BRCA). ionizing radiation (IR) could induce the death of cancer cells, however, if IR could induce ferroptosis in BRCA and how it works, still remains unknown. Bioinformatics analysis were performed to screen ferroptosis-related genes differentially expressed in BRCA tumor tissue and normal tissue. Then BRCA cell lines with different estrogen receptor (ER) phenotypes were used for studies in vitro, including ER‐ positive (MCF‐7 and ZR‐75-1) and ER‐negative (MDA‐MB‐23) cells. The dynamic changes of mRNA and protein levels were examined after X-ray of 8Gy (3Gy/min) by qRT-PCR and Western blotting respectively. Immunoprecipitation (IP) was used to explore the interaction between proteins. Luciferase assay was used to analyze the transcriptional regulation effect of ESR1 on SLC7A11. Cell death were analyzed by trypan blue staining followed by flow cytometry. The result showed that ferroptosis- related gene SLC7A11 was higher in BRCA tissues compared with normal tissues and associated with poor survival. A positive correlation exists between ESR1 and SLC7A11 expression. ESR1 functioned as transcription factor and promoted SLC7A11 expression at the early stage after IR. ESR1/SLC7A11 knockdown significantly enhanced IR-induce ferroptosis in ER-positive cells. At 12 h after IR, the IP data showed the interaction between E3 ubiquitin ligase NEDD4L and SLC7A11, followed by the ubiquitylation and degradation of SLC7A11 (24 h after IR). Thus, SLC7A11 expression was regulated by both ESR1and NEDD4L, in opposite way. For the first time we elucidated that ESR1 and NEDD4L functioned together after radiation treatment and finally induced ferroptosis in BRCA cells, which provides novel insight for the guidance of clinical treatment of BRCA.